Microbial density in Azadirachta indica A. Juss. and Tectona grandis L.f. based agroforestry systems in north-eastern tropical Karnataka, India - ., Doddabasawa; Chittapur, B.M.; ., Pampangouda; Gurumurthy, H. (Indian Journal of Agroforestry, 2020)
Intensified agriculture is becoming unsustainable due to land degradation, loss of soil fertility and productivity however agroforestry could help in reversing the trend. The present study, therefore, was carried out during 2016-17 tounderstand the influence of agroforestry systems on microbial density and soil chemical properties in neem (Azadirachta indica)- and teak (Tectona grandis)-based agroforestry systems under rainfed and irrigated ecosystems, respectively. The microbial density under neem-based agroforestry was significantly higher in boundary plantation, followed by scattered plantation and bund plantation, and significantly lower density was noticed in crop based farming system. On the other hand, under teak-based agroforestry, higher microbial density was recorded in block plantation, followed by silvi-horti, boundary plantation and bund plantation while it was again the lowest in crop based farming system. Further, significant positive correlations occurred between microbial density and soil organic carbon and nitrogen contents. Density of trees in agroforestry revealed significant influence on microbial density in both the ecosystems. In conclusion, the results indicated that agroforestry systems, traditional or adopted, and whether rainfed or irrigated appear important from the point of soil biota particularly soil microbes and soil health and production sustainability in the semi-arid tropics.